Perbedaan Tingkat Pengetahuan Pencegahan Kanker Serviks SMA Negeri dan Swasta Kelas X Kabupaten Badung : knowledge level on cervical cancer prevention among class X high school female students in public versus the private schools within the Badung Regency. - Ni Wayan Armerinayanti; Ni Luh Putu Eka Kartika Sari; Made Intan Ryani Putri (Aesculapius Medical Journal, 2022)
The average age for first having sexual intercourse outside of marriage, which is 14-19 years, is one of the causes of the risk of cervical cancer. This research compares the knowledge level on cervical cancer prevention among class X high school female students in public versus the private schools within the Badung Regency. A cross-sectional comparative study is used as the study designed, which includes a total sample of 336 female students (n=336) by utilizing questionnaires. Bivariate analysis with Interdependent T-test and Statistical Package for Social Sciences (SPPS) is appropriate for analyzing the gathered research data. The results of this study between public and private high schools in Badung Regency have different levels of knowledge about cervical cancer prevention. Data analysis shows that 99 (29.5%) female respondents in public high schools know about cervical cancer prevention, and only 80 (23.8%) female students from private schools. The findings of this study imply that school-based teaching is critical for increasing understanding and lowering cervical cancer rates, as well as collaborating with the health department to provide cervical cancer counseling and installing health-related information media in the school environment.